Optimization studies on mixing of curd and ingredients during Lassi (Stirred Curd) manufacturing - Datir, Rupesh Prabhudas; Ravindra, Menon Rekha; Manjunatha, M.; Sharma, Monika (Indian Journal of Dairy Science, 2022)
Consumption of the fermented milk is on the rise due to its therapeutic benefits to human health. Several processes and technologies evolved to further enrich the fermented foods. In the present study, an Indian fermented milk product Lassi (sweet stirred curd) was selected for the experimental trials and optimized for the different process conditions. Lassi was prepared by adding sugar and water in curd and mixing them in the prefabricated mixing vessel. Three different impellers were tested in the preparation of Lassi. Two independent factors, namely off-bottom clearance (OBC) and impeller speed (IS) were selected to optimize the process conditions to yield a uniform good quality product. The quality of the finished product was assessed by sensorial and rheological attributes. Performance of the impeller was estimated by evaluating the mixing time, mixing index and power consumption. Three levels of OBC (3, 6, 9 cm) and IS (300, 400, 500 rpm) respectively were selected. Experiments were designed as per response surface methodology and accordingly trials were conducted. Constraints were optimized by setting up the goal for each of them. Based upon the solutions provided by the software, the product was prepared keeping the impeller positioned at 4.8 cm OBC and rotational speed of 389 rpm. The prepared product was validated against the experimental values and found no significant difference between theoretical and experimental values. Results indicated that the multivane churn impeller was found to be suitable for the preparation of good quality lassi. Mixing time and power consumption were optimized at 160±17.32 and 34.21±0.70, respectively. Overall acceptability of the product was 8.16±0.153 on 9-point hedonic scale. It can be concluded that the developed unit and impeller was able to deliver a uniform quality product with minimum mixing time and power consumption.